Improving Students’ Reading Comprehension Through “KWL Plus” Technique at SMAN 2 Kampar - Zalisman Zalisman; Riki Astafi (STAIN Bengkalis, 2021)
The objective of this research is to find out the significant improvement of using KWL Plus technique in comprehending reading text. Thus, to find out the improvement of students’ reading comprehension, the writer carried out experimental research, which focused only in experimental class. The writer used KWL Plus technique that consisted of some steps. First, the students must completed KWL grid that consists of three columns. Then, the students made concept map based on information from KWL grid. After that, they wrote a summary based on concept map. The sample of this research are thirty five students. The research has been conducted from May to June 2020 at the first year students of SMA N 2 Kampar. In collecting data, the writer gave reading texts in form of multiple choice tests that consists of 30 questions to the sample of experimental class. After giving the test to the sample, the writer collected the answer sheets to be calculated for the data. The obtained data was analyzed by using the formula of t-test in Hatch and Farhady Book (1982:105). It was found that t-calculated was 7.06 and t-table on the level of significant 5% or 0.05 and degree of freedom (df) 34 was2.042. It was seen that Tc>Tt. It means that null hypothesis (Ho) is rejected and alternative hypothesis (Ha) is accepted. In other words by using KWL Plus technique was able to give positive contribution to improve students’ achievement in reading comprehension at the first year students of SMA N 2 Kampar.